The supplementation of a high dose of fish oil during pregnancy and lactation led to an elevation in Mfsd2a expression without any changes in docosahexaenoic acid levels in the retina of healthy 2-month-old mouse offspring - Macura, Irena Jovanovic; Djuricic, Ivana; Major, Tamara; Milanovic, Desanka; Sobajic, Sladjana; Kanazir, Selma; Ivkovic, Sanja (Frontiers in Nutrition, 2024)
During fetal development, the proper development of neural and visual systems relies on the maternal supplementation of omega-3 fatty acids through placental transfer. Pregnant women are strongly advised to augment their diet with additional sources of omega-3, such as fish oil (FO). This supplementation has been linked to a reduced risk of preterm birth, pre-eclampsia, and perinatal depression. Recently, higher doses of omega-3 supplementation have been recommended for pregnant women. Considering that omega-3 fatty acids, particularly docosahexaenoic acid (DHA), play a crucial role in maintaining the delicate homeostasis required for the proper functioning of the retina and photoreceptors the effects of high-dose fish oil (FO) supplementation during pregnancy and lactation on the retina and retinal pigmented epithelium (RPE) in healthy offspring warrant better understanding. Our study demonstrated that despite the high-dose FO treatment during pregnancy and lactation, the rigorous DHA homeostasis in the retina and RPE of the two-month-old offspring remained balanced. Another significant finding of this study is the increase in the expression levels of major facilitator superfamily domain-containing protein (Mfsd2a), a primary DHA transporter. Mfsd2a also serves as a major regulator of transcytosis during development, and a reduction in Mfsd2a levels poses a major risk for the development of leaky blood vessels. Impairment of the blood-retinal barrier (BRB) is associated with the development of numerous ocular diseases, and a better understanding of how to manipulate transcytosis in the BRB during development can enhance drug delivery through the BRB This is a provisional file, not the final typeset article or contribute to the repair of central nervous system (CNS) barriers. Therefore, high-dose FO supplementation could be considered for fortifying the retinal blood vessels during development.